Synthesis of Emulsifier from Refined Bleached Deodorized Palm Stearin by Chemical Glycerolysis in Stirred Tank Reactor - Puspita Arum, A; Hidayat, C; ., Supriyanto (KnE Life Sciences, 2019)
Emulsifiers are widely used in the food and beverage industry, especially the mixture of mono- and diacylglycerol. They are produced from glycerolysis reaction using chemical catalysts because of fast reaction time, high conversion of reactants and low cost. Palm stearin is abundant and less utilized. Therefore, palm stearin is used as raw material for the synthesis of emulsifiers. The goal of this project was obtained emulsifier containing high concentrations of mono- and diacylglycerol. Synthesis of emulsifier was conducted with reaction time (1 h to 12 h), catalyst concentration (1 %, 2 %, 3 %, and 4 %) (w/w) and addition of molecular sieve (12 % (w/w) and without as control). Furthermore, products were fractionated at various temperatures (40 ∘C, 30 ∘C, 20 ∘C, and 10 ∘C). These results suggest that the best conditions for the synthesis of mono- and diacylglycerol from palm stearin using NaOH catalyst in Batch stirred Tank Reactor are NaOH concentration 3 % (w/w), reaction time 6 h, molecular sieves 12 % (w/w), reaction temperature 90 ∘C, addition of tert-butanol as solvent 2 mL ⋅ g −1 of oil, palm stearin: glycerol molar ratio (1 : 5), the speed of the stirrer of 400 rpm. The fractionation temperature is 30 ∘C with product yield is 61.43 % which contains 91.00 % ± 2.50 % and 9.00 % ± 2.50 % of monoand diacylglycerol, respectively. Characteristic of emulsifiers are emulsion capacity 95.55 % ± 0.71 %, emulsion stability 90.44 % ± 1.24 %, HLB value 10.25 ± 0.44, melting point 62.67 ∘C ± 2.52 ∘C to 70.33 ∘C ± 0.58 ∘C and type of emulsion is oil in water (o/w). Keywords: Emulsifier, Glycerolysis, Mono- and diacylglycerol, NaOH, Palm stearin